2015
DOI: 10.3390/met5031414
|View full text |Cite
|
Sign up to set email alerts
|

A Computationally-Efficient Numerical Model to Characterize the Noise Behavior of Metal-Framed Walls

Abstract: Architects, designers, and engineers are making great efforts to design acoustically-efficient metal-framed walls, minimizing acoustic bridging. Therefore, efficient simulation models to predict the acoustic insulation complying with ISO 10140 are needed at a design stage. In order to achieve this, a numerical model consisting of two fluid-filled reverberation chambers, partitioned using a metal-framed wall, is to be simulated at one-third-octaves. This produces a large simulation model consisting of several m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

7
2

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 15 publications
(22 reference statements)
1
13
0
Order By: Relevance
“…The implant design presented in this paper shows a Young's Modulus of 14.58 GPa (experimental) which is closer to the lowest value of Young's Modulus of cortical bone (18)(19)(20)(21)(22)(23)(24)(25). The slightly lower Young's Modulus of the presented implant in comparison with bone is beneficial to accelerate the process of osteointegration (36).…”
Section: Discussionsupporting
confidence: 63%
“…The implant design presented in this paper shows a Young's Modulus of 14.58 GPa (experimental) which is closer to the lowest value of Young's Modulus of cortical bone (18)(19)(20)(21)(22)(23)(24)(25). The slightly lower Young's Modulus of the presented implant in comparison with bone is beneficial to accelerate the process of osteointegration (36).…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, the validation study showed the current VoI represents an adequate ratio (internal/external) for the six UC arrangements considered in this study. Furthermore, a larger than required fluid domain will increase solution time, which is widely considered inefficient numerical modelling [86][87][88][89].…”
Section: Flow Simulation and Permeabilitymentioning
confidence: 99%
“…Lightweight structures that combine high structural stiffness, energy absorption [1][2][3] and acoustic performance [4][5][6][7][8] are of interest to automotive, aerospace and the construction sectors. Automotive floor panels [9] and aerospace bulkheads [10] are examples of mechanical structures where the secondary function extends to providing adequate acoustic comfort.…”
Section: Introductionmentioning
confidence: 99%